Analisis Dampak Sosial Dan Ekonomi Dalam Pembangunan Jembatan Surabaya Di Kelurahan Kenjeran Kecamatan Bulak Kota Surabaya - Sri Umiyati; Dwi Kartini, Supriyanti; Wahyudi, Agus (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
Infrastructure development has a very vital role in fulfilling people's basic rights. Infrastructure or facilities and infrastructure have a very strong relationship with the social and economy in an area. As a result, these cities will experience systemic social and economic changes and will become a magnet for the community to look for business and employment opportunities and reside. The city of Surabaya is active in terms of tourism, one of which is a new icon in East Surabaya, namely the existence of the Surabaya Bridge. The purpose of this study is to describe and analyze the social and economic impacts arising from the Surabaya Bridge. The method used in this study is descriptive qualitative which refers to the process of analyzing social impacts and economic impacts. Data collection techniques of this study are primary data, namely data obtained directly from informants through interviews and also secondary data obtained from newspapers and online media that discuss the construction of the Surabaya Bridge. The data analysis technique used in this study is the interactive data analysis model of Miles and Huberman. This model consists of three main things, namely data reduction, data presentation, and conclusion / verification The results of this study indicate that there is a social impact through social change in the community including changes in the social value of the community and community participation. The economic impact felt by citizens is the increasing number of opportunities to open a business so that it adds to the family's economic value including community income/income and open new business opportunities.